Improving Students’ Reading Comprehension Using Pictuures On Report Texts - Rospin Hidayati (Lembaga Penelitian dan Pendidikan Mandala, 2019)
Abstract. The objectives of this research was to find out the whether using picture in improving students reading ability for the eleventh grade students of MA NW Pringgasela is effective and to find out significant differences in the reading skill between the students who were tauhgt by using picture and those who are not taught by using it.This research was an experimental research. The participant of the research were the tsudents of the eleventh grade of MA NW Pringgasela. Class Xia as an experimental group and class Xib as a control group. The research instrument used by the wriiter was in the form of reading comprehension test. The data in this research were mainly gathered through the test pre-test and post-test. The pre-test was administrated to see the student’s ability in reading comprehension before using picture were used. The post-test was administrated to see the student’s progress in reading comprehension. After the data was collected, the researcher then analyzed them by using t-test to see whether there was any significant difference in reading comprehension after using picture were aplied.in teaching reading to students of MA NW Pringgasela eleventh grade Xia and Xib. The mean score of experimental group in pre test was 61.5 while the mean score for the control group was 61.1. meanwhile, after using picture on report text The findings of the research show that first using picture was effective to be used were used, their reading skill got improved. It can be inferred from the result of the students post test. In the post test, the mean score for the experimental group changed to 79.5. The t-test showed a significantt difference in teaching reading after using picture on report text. Finally, it could be concluded that using picture was good in teaching reading on report text, and the use of it could improve the students’ ability in reading. Teachers can use it as a media in teaching reading. It can also give information for readers and become reference for other researchers